2004
DOI: 10.1097/01.brs.0000131218.35875.ed
|View full text |Cite
|
Sign up to set email alerts
|

A Cochrane Review of Manipulation and Mobilization for Mechanical Neck Disorders

Abstract: Mobilization and/or manipulation when used with exercise are beneficial for persistent mechanical neck disorders with or without headache. Done alone, manipulation and/or mobilization were not beneficial; when compared to one another, neither was superior. There was insufficient evidence available to draw conclusions for neck disorder with radicular findings. Factorial design would help determine the active agent(s) within a treatment mix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
146
1
15

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(167 citation statements)
references
References 52 publications
2
146
1
15
Order By: Relevance
“…Those authors also included the trial by Howe et al 58 ; however, this study did not include a group receiving only manipulation, thus we excluded it from our review. Gross et al [36][37][38] conducted a pooled analysis of Vernon et al 55 and Sloop et al 54 , given that they were clinically comparable and not statistically heterogeneous. Outcome measures were pooled despite the fact that Vernon et al 55 obtained only pressure algometry readings, not pain scores, at 5 minutes post-intervention and included a mobilization group, while Sloop et al 54 obtained pain outcome only at 3 weeks post-intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those authors also included the trial by Howe et al 58 ; however, this study did not include a group receiving only manipulation, thus we excluded it from our review. Gross et al [36][37][38] conducted a pooled analysis of Vernon et al 55 and Sloop et al 54 , given that they were clinically comparable and not statistically heterogeneous. Outcome measures were pooled despite the fact that Vernon et al 55 obtained only pressure algometry readings, not pain scores, at 5 minutes post-intervention and included a mobilization group, while Sloop et al 54 obtained pain outcome only at 3 weeks post-intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In recent Cochrane reviews, Gross et al [36][37][38] included 4 single-session studies, three of which 50,54,55 were included in this review. Those authors also included the trial by Howe et al 58 ; however, this study did not include a group receiving only manipulation, thus we excluded it from our review.…”
Section: Discussionmentioning
confidence: 99%
“…11 In comparison, a large amount of studies supports the use of manipulation in both acute and chronic musculoskeletal syndromes related to the spine. [12][13][14][15] It should be emphasized that nowhere does this study state or imply that chiropractic manipulation should be used only for symptomatic patients without identifiable joint restrictions. The purpose of this pilot study was to investigate the effect of chiropractic treatment on hip joint extension ability and running velocity in young runners with identifiable joint restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of the effectiveness of HVLA SM and mobilization for mechanical neck disorders revealed that HVLA SM and/or mobilization when done alone was not beneficial and that, when compared with one another, neither was superior. 3 High-velocity, low-amplitude spinal manipulation is commonly used by manual therapists and doctors of chiropractic to treat spinal pain; but it is also commonly associated with minor transient adverse reactions such as local pain and stiffness, fatigue, or headaches. Observational studies have investigated the frequency and percentage of patients who experience these minor transient adverse reactions.…”
Section: Introductionmentioning
confidence: 99%